Long-term outcomes of flap reconstruction for hardware exposure in low-energy distal tibia fractures - Eleni Karagergou; Dimitrios Kitridis; Ektoras Kessidis; Nikolaos Platon Sachinis; Alexandros Givissis; Panagiotis Givissis (JPRAS Open, 2025)
Wound dehiscence and hardware exposure are significant complications following open reduction and internal fixation (ORIF) of low energy distal tibia and ankle fractures. This study aims to evaluate the long-term outcomes after removal of the exposed implants, application of an Ilizarov framework when needed and flap reconstruction.A prospective case series study was conducted, including eight patients with wound breakdown and exposed hardware following ORIF for closed distal tibia and ankle fractures since January 2022. Data collection consisted of patients’ demographics, characteristics of the initial injury, wound microbiology and subsequent management. Patients were treated with removal of exposed implants, application of Ilizarov framework in cases of nonunion and flap reconstruction. Outcomes were assessed at 2 years postoperatively. The primary outcome measure was the percentage of clinical and radiological bony union, while secondary outcomes included wound complications, chronic osteomyelitis and patient-reported satisfaction using the LIMB-Q™ questionnaire.The mean time from ORIF to removal of metal work was 8.3 weeks. Ilizarov framework was placed in five patients due to nonunion at the fracture site. A local propeller flap was selected and satisfactory wound coverage was achieved in all cases. The rate of bony union was 75 % at 2 years of follow-up. One patient developed chronic osteomyelitis and another one refractured his tibia. In terms of patient satisfaction, the appearance of the leg rated low, followed by function and patients’ expectations.Once hardware exposure following ORIF for closed low energy distal tibia and ankle fracture is encountered, local flap reconstruction and targeted antibiotic therapy are essential for eradication of infection and promotion of bony union. Removal of hardware and replacement with an external fixation system are mandatory for late infections, although it should be re-considered in earlier infections, where hardware maintenance and suppression of infection may be equally effective as an alternative treatment.